PENGEMBANGAN MEDIA PEMBELAJARAN IPA DENGAN ANIMASI MACROMEDIA FLASH BERBASIS MODEL PENGAJARAN LANGSUNG (DIRECT INSTRUCTION) DI SEKOLAH DASAR - Kusumawati, Naniek (Premiere Educandum, 2015)
This research is the development of instructional media developed macromedia flash animation-based teaching model directly in SDN Mangkujayan II Ponorogo. Based on the research got enthusiastic excellent student this is evidenced by the results of the data questionnaire responses following students on learning to use media such as macromedia flash animation, developed the data obtained by 36 students (100% ) expressed interest. Data questionnaire responses of students to the language used in textbooks and media animation data obtained by 32 students (88.9%) expressed understandable and 4 students (11.1%) said it was difficult to understand. Data questionnaire responses of students to the illustrations in textbooks and media animation data obtained by 35 students (97.2%) expressed delight and 1 student (2.7%) were not happy. Mastery of student learning outcomes after the use of instructional media macromedia flash animation-based teaching model directly based on analysis of data on student learning outcomes results obtained by 28 students completed the individual, the individual is not finished 8 students from 36 students who take the post-test. Mastery of cognitive learning outcomes for students in classical 77.78%. This means that students of class V have achieved mastery of learning outcomes are classical. Keyword:        Macromedia Flash Animation, Models Direct Instraction, Completeness Learning Outcomes